Zasady wnoszenia opłat na rzecz komisji bioetycznych w wieloośrodkowych badaniach klinicznych produktów leczniczych - Brzezicki, Paweł (Kwartalnik Prawa Publicznego, 2012)
The article presents legal analysis concerning principles of paying fees for research ethics committees (in Poland so-called bioethics committees – hereinafter referred to as REC) in multi-centre clinical trials. The topic concerned engenders many doubts in the legal turnover. At first, author considers juridical nature of REC, since its legal character is still not clearly determined, and refers to judicial decisions. The following part is devoted to interpretation of legal principles regarding financial aspects of REC system functioning. The right of so called participating REC (committee which passes its judgment on particular researchers and research sites, but not on the clinical trial as a whole) to remuneration (share in total fee) and rules of its calculation and collection constitute the essential problem of this part of ruminations. The author lays down his own approach to the discussed subject matter and draws his own conclusions Last but not least the article poses more fundamental question whether the currently existing legal solutions are appropriate from the perspective of independence of RECs.